Unidade jurisdicional em Santarém/PA: a percepção de atendimento das vítimas de violência doméstica - SANTOS, Wivian Narla Teixeira dos (Universidade Federal do Oeste do Pará, 2024)
Violence against women is not new; in fact, the opposite is as old as humanity itself. What is recent is the concern to change this type of gender-based violence. In view of this problem, the reason that led me to carry out this research focused on domestic violence was mainly to see the increase of this violence broadcast in the television media, printed as newspapers and magazines, in addition to living and witnessing close people who suffer the most diverse types of aggressions, which sparked interest in developing a study on the theme of domestic violence with a focus on the jurisdictional unit in Santarém-PA: The perception of care for victims of domestic violence. This aimed to understand the perception of victims of domestic violence about the care received by them by the Jurisdictional Unit in Santarém, and also the advances in the trajectory of care by the justice system in the face of cases of domestic violence. The methodological procedures used were bibliographic research as a tool for understanding the concepts of domestic violence and their experiences within the process of assistance through the justice system, complemented with the document search in locus at the Santarém Forum, more specifically in the violence staff domestic and family, having as research participants victims who were on the domestic violence stick during the collection. The results of the research are organized by presenting the graphs of the quantitative data on the number of cases in the domestic violence court - Santarém, in the chronological order of application, and ending with the analysis of the Interview Guide. After analyzing the reports of the victims selected to participate in the research, it was found that although they feel welcomed by the system, the practical result shows that in most cases, there is a recurrence of aggression.